Mendidik Toleransi Beragama Siswa; Analisis Tentang Efektivitas Layanan Informasi Menggunakan Media Film - Wastuti, Sri Ngayomi Yudha; Ramadhani, Nadya Suci (Sekolah Tinggi Agam Islam Sumatera Medan, 2022)
This study aims to analyze teacher activities in educating religious students on religious tolerance, which is packaged through information services using film media. In this research, the film used is The Santri film by director Livi Zheng, released in 2019. The research location is in MTs. Insan Cita Medan, with research informants, focused on class VIII. This study uses quantitative research methods with a quasi-experimental approach. The research sample was 30 students, determined by purposive sampling. Data collection using questionnaires and interviews. Questionnaire to obtain data about information services and consultations to determine student responses to these services. Test the hypothesis made with the Product Moment formulation and for its significance using the t-test. The study results show a significant positive effect of information services using film media on religious tolerance in students VIII MTs. Insan Cita Medan Learning Year 2021/2022 with a correlation index of r-count = 0.7155 > r-table = 0.334 and a significant level of 51.19%. Thus the better the information services provided, the better the changes in the attitude toward religious tolerance of students.